Penentuan Nilai Computed Tomography Dose Index (CTDIvol) dan Dose Length Product (DLP) Pesawat CT-Scan kepala pada kasus Stroke Non Hemoragik (SNH): Determination of Computed Tomography Dose Index (CTDIvol) and Dose Length Product (DLP) values of head CT-Scan aircraft in cases of Non Hemorrhagic Stroke (SNH) - Nabilla Fatimah; Gusti Ngurah Sutapa; Wayan Balik Sudarsana; Ni Nyoman Ratini; Putu Suardana; I Ketut Putra (Kappa Journal, 2024)
A study was conducted on the determination of Computed Tomography Dose Index (CTDIvol) and Dose Length Product (DLP) values of head CT-Scan aircraft in cases of Non Hemorrhagic Stroke (SNH). The study was conducted at the Radiology Installation of Prof.Dr. I.G.N.G. Ngoerah Denpasar Hospital using secondary data from head CT-Scan examination results consisting of age, gender, kV, mAs, slice thickness, rotation time, CTDIvol and DLP in patients aged 40-80 years. This study aims to determine the local DRL value at Prof.Dr. I.G.N.G. Ngoerah Denpasar Hospital does not exceed the national DRL value. It was found that in female patients the CTDIvol value in male patients was 54.9 mGy and in female patients it was 53.11 mGy. While the DLP value of male patients was 1143 mGy.cm and in female patients it was 1118 mGy.cm. Based on the results of the analysis with a one-way t-test, it can be seen that the DRL values of CTDIvol and DLP in both male and female patients do not exceed the standards set by BAPETEN No.1211/K/V/2021, so it can be said that the CT-Scan at the Radiology Installation of Prof.Dr. I.G.N.G. Ngoerah Denpasar Hospital is still suitable for use in examinations, especially head examinations.